The Influence of Digital Marketing and Product Innovation on Marketing Performance with Government Support as a Moderating Variable: A Study on Micro Culinary Enterprises in Depok City - Roihatul Jannah; Daman Sudarman (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
This study aims to analyze the influence of digital marketing and product innovation on the marketing performance of micro culinary businesses in Depok City, with government support as a moderating variable. The background of this research stems from the importance of optimizing digital-based marketing strategies and product innovation to enhance MSME competitiveness, especially amid high market competition and changing consumer behavior. This research employed a quantitative methodology, utilizing surveys to collect data from 101 micro culinary business owners who were chosen using purposive sampling techniques. The data was analyzed through Structural Equation Modeling using the Partial Least Squares method via SmartPLS software. Findings revealed that digital marketing significantly and positively influences marketing performance, demonstrated by a path coefficient of 0.554. However, product innovation did not demonstrate a statistically significant impact on marketing performance. Additionally, government support failed to serve as a meaningful moderator in the relationships between both digital marketing and product innovation with marketing performance outcomes. Overall, the model explains 38.6% of the variation in marketing performance. These findings indicate that digital marketing strategy is a key factor in improving MSME marketing performance, while the role of product innovation and government intervention has not yet provided strong statistical contribution in the context of this study.